Upaya Meningkatkan Hasil Belajar Siswa dan Retensinya Menggunakan Metode Mnemonics - Nisa Dhania Atimi; Asriah Nurdini Mardiyya Ningsih; Erni Lestari (Jurnal Studi Guru dan Pembelajaran, 2023)
The mnemonic method is a powerful technique for memorizing the subject matter we study. This study aims to determine the effect of using the mnemonic method on male reproductive system material on student learning outcomes and retention. This classroom action research involved 30 class XI students of SMAN 10 Pontianak for the 2022/2023 academic year. It uses two learning maintenance cycles. Two male reproductive system lesson plans, two Likert scales for observing teacher performance, and two achievement tests were administered in this study. The research results show that the average score of student learning achievement increased from 56.0 to 81.0. The percentage of learning completeness is 83.3%. In addition, some students' notes use mnemonic techniques. It was concluded that the mnemonic technique succeeded in increasing student learning outcomes and their retention (in the high category) in the male reproductive system material. Some recommendations are that this technique should be used by teachers in schools